MP-17 Avian Influenza Virus-H5N1 Is Circulating Among Backyard Chicken in Marga District, Tabanan Regency, Bali - Gusti Ayu Yunianti Kencana; I Nyoman Suartha; I Made Kardena (Hemera Zoa, 2018)
Avian Influenza or bird flu is ani nfectious pandemic disease (Horimoto and Kawaoka, 2001). AI viruses can cause high mortality in poultry and infect humans in Indonesia (Daniels et al., 2013). Pet and backyard animals can be infected with the HPAI-H5N1 virus (Mahardika et al., 2018). Monitoring of the virus needs to be done so that the Avian Influenza outbreak casesare not occurred. Isolation of AI virus can be done on 9-day-old hatched chicken eggs injected through the allantois’ space. The virus can be tested by hemagglutination (HA/HI) and Reverse Transcriptase Polymerase Chain Rection (RT-PCR) tests (FAO, 2014).